Bioremediation of textile dye wastewater using microalgae: current trends and future perspectives. Issue 12 (19th July 2021) - Premaratne, Malith; Nishshanka, GKSH; Liyanaarachchi, VC; Nimarshana, PHV; Ariyadasa, Thilini U
Abstract: Wastewater generated from the textile industry contains numerous pollutants, most notably dyes, which can cause adverse effects, including negative impact on aesthetics, eutrophication, decrease of photosynthetic activity and bioaccumulation of toxins in aquatic ecosystems, if discharged without adequate treatment. The cultivation of microalgae in the textile dye effluent has been identified as a promising alternative to conventional methods of wastewater treatment. During microalgae cultivation, dyes present in effluent are remediated through bioconversion/biodegradation or biosorption. Thus, treatment using microalgae reduces the color and nutrient load of textile effluent, which mitigates numerous negative environmental impacts caused by its discharge into the natural environment. Furthermore, compared to conventional treatment processes, use of microalgae for bioremediation of textile effluent provides the added advantage of generating valuable biomass that can be processed into bioproducts, biofuels and bioenergy. Wastewater‐integrated cultivation would enhance the sustainability of microalgal biomass production by reducing the freshwater footprint and recovery of waste nutrients from effluent, thereby promoting the concept of a biobased economy. In this mini‐review, the current status and future perspectives of using microalgae for bioremediation of textile dye wastewater were analyzed, with focus on various strategies reported in the literature. A critical review of the literature showed that most studies focused on wastewater treatment, while exploring applications for concomitantly generated biomass was a secondary consideration. Hence, the requirement of a paradigm shift in current research for valorization of microalgal biomass was highlighted. Moreover, it was concluded that comprehensive feasibility studies are necessary prior to industrial‐scale bioremediation of textile dye effluent. © 2021 Society of Chemical Industry (SCI).